A biosynthetically inspired route to substituted furans using the Appel reaction: total synthesis of the furan fatty acid F5. Issue 47 (26th May 2017) - Lee, Robert J.; Lindley, Martin R.; Pritchard, Gareth J.; Kimber, Marc C.
Abstract : Appel reaction conditions have been harnessed to affect a mild biosynthetically inspired dehydration of endoperoxides to deliver multi-substituted electron rich furans. Abstract : Appel reaction conditions have been harnessed to affect a mild biosynthetically inspired dehydration of endoperoxides to deliver multi-substituted electron rich furans. Unlike traditional dehydrative procedures, this method is metal and acid free, and can be achieved under redox neutral conditions. It is general for a range of aryl and alkyl substituted endoperoxides, and is functional group tolerant. Furthermore, this procedure has been used to deliver an effective total synthesis of the furan fatty acid (FFA) F5 .